Fluorescent probe for high‐throughput screening of membrane protein expression. (3rd July 2013) - Backmark, A. E.; Olivier, N.; Snijder, A.; Gordon, E.; Dekker, N.; Ferguson, A. D.
Abstract: Screening of protein variants requires specific detection methods to assay protein levels and stability in crude mixtures. Many strategies apply fluorescence‐detection size‐exclusion chromatography (FSEC) using green fluorescent protein (GFP) fusion proteins to qualitatively monitor expression, stability, and monodispersity. However, GFP fusion proteins have several important disadvantages; including false‐positives, protein aggregation after proteolytic removal of GFP, and reductions in protein yields without the GFP fusion. Here we describe a FSEC screening strategy based on a fluorescent multivalent NTA probe that interacts with polyhistidine‐tags on target proteins. This method overcomes the limitations of GFP fusion proteins, and can be used to rank protein production based on qualitative and quantitative parameters. Domain boundaries of the human G‐protein coupled adenosine A2a receptor were readily identified from crude detergent‐extracts of a library of construct variants transiently produced in suspension‐adapted HEK293‐6E cells. Well expressing clones of MraY, an important bacterial infection target, could be identified from a library of 24 orthologs. This probe provides a highly sensitive tool to detect target proteins to expression levels down to 0.02 mg/L in crude lysate, and requires minimal amounts of cell culture.